Sistem Pendeteksi Gas Amonia (Nh3) Untuk Keamanan Ruang Produksi Pada Industri Pengolahan Udang Berbasis Arduino - Burhanuddin Nur; Untung Suryadhianto; Charis Fathul Hadi (ZETROEM, 2022)
Obtain the design ammonia gas detection system (NH3) for and obtain information on the performance of the ammonia gas detection system (NH3) for the safety of the production room in the Atmega 328P-based shrimp processing industry. The software design will be carried out in research includes software design for the microcontroller to the LCD and the fan circuit. The microcontroller software of instructions that will be executed by the microcontroller for controlling ADC, LCD and fan circuits. This research software is made using the BASCOM language and the AvrOsp II compiler. The design of the ammonia gas detection system (NH3) for the safety of the production room in the Arduino-based shrimp processing industry can already be used because it has passed a feasibility test on the user and design aspects which include the efficiency and level of accuracy of the sensor on the Arduino-based Ammonia gas detection system. and obtained a value of 91.7% with a decent category. The feasibility test of all aspects assessed can be categorized as feasible with a percentage of 90.5%.